Biochemical constituents and insecticidal activities of Callistemon viminalis essential oil against adults and eggs of Pediculus humanus capitis (Phthiraptera: Pediculidae) - Manachai Yingklang; Aroonsri Priprem; Natsajee Nualkaew; Bunleu Sungthong; Porntip Pinlaor; Somchai Pinlaor (Elsevier, 2022)
Background: Synthetic chemical pediculicides used for head-louse treatment do not kill louse eggs, can induce side effects in humans, and lead to genetic resistance in lice worldwide, including in Thailand. Use of phytoconstituents, particularly plant-derived essential oils, is alternatively recommended for head lice. Purpose: To identify biochemical constituents of Callistemon viminalis essential oil (EO) and to assess the ex vivo effects of EO on head lice and their eggs. Methods: The EO was extracted from fresh leaves C. viminalis by stream distillation, and the biochemical constituents were identified by gas chromatography-mass spectrometry (GC-MS). Louse samples were collected from schools in Khon Kaen Province, Thailand for ex vivo tests. Pediculicidal activity of EO was investigated using topical contact, and ovicidal activity was assessed using immersion and topical tests. Adult lice were observed for 8 h after treatment and eggs were observed for 3 weeks to assess pediculicidal and ovicidal effects, respectively. Mortality was noted and morphological change was recorded for head lice using scanning electron microscopy. Inhibition of egg hatching was evaluated. Results: Forty-four phytochemical components were identified in EO obtained from fresh leaves of C. viminalis. The most abundant were 1,8-cineole (66.96%), α-pinene (18.74%) and o-cymene (7.02%). Ex vivo, C. viminalis EO at concentrations above 10% for 30 min caused 100% adult mortality using a topical bioassay. In a complete-immersion test, all head louse eggs failed to hatch after exposure to concentrations of C. viminalis EO of 10% or greater for 10 min. Eggs were less sensitive using a topical method. Permethrin 1%, coconut oil and distilled water exhibited low efficacy against both crawling and egg stages. Scanning electron micrographs indicated that C. viminalis EO caused obstruction in some louse spiracles but had no effect on the cuticle or sensory hairs. Conclusion: The EO derived from C. viminalis had higher ex vivo efficacy against head lice and their eggs than 1% did permethrin. This EO may be a starting point for developing natural pediculicides to control head lice that are susceptible or resistant to permethrin.